Intraoperative electron beam radiotherapy for locoregionally persistent or recurrent head and neck cancer. Issue 7 (19th February 2019) - Wald, Patrick; Grecula, John; Walston, Steve; Wei, Lai; Bhatt, Aashish; Martin, Douglas; Bonomi, Marcelo; Rocco, James; Old, Matthew; Teknos, Theodoros; Blakaj, Dukagjin
Abstract: Background: To report our institutional experience with intraoperative radiotherapy for persistent or recurrent head and neck cancer. Methods: Sixty‐one patients were treated with salvage surgery and intraoperative radiation therapy (IORT). Fifty‐eight patients (95%) had previously received external beam radiotherapy (EBRT) as a component of their definitive therapy. Forty‐four patients (72%) had squamous cell carcinoma (SCC). Surgical margins were positive in 28 patients (46%). IORT was prescribed to a median dose of 12.5 Gy (range, 10‐17.5). Twenty‐three patients (38%) received a course of postoperative EBRT (median 45 Gy). Clinical outcomes were retrospectively reviewed and univariate analysis was performed using log‐rank tests to correlate clinical outcomes with histology, surgical margin, and adjuvant therapy. Results: Median follow‐up among surviving patients was 15.9 months. Median progression‐free survival (PFS) and overall survival (OS) were 9.8 and 19.1 months, respectively. One‐ and 2‐year rates of locoregional control (LRC) were 59% and 35%, respectively. One‐ and 2‐year rates of PFS were 39% and 19%, respectively. One‐ and 2‐year rates of OS were 62% and 42%, respectively. Overall survival was better for non‐SCC histology ( P  = .03). For SCC patients, negative surgical margin showed a trend toward improved PFS ( P  = .09) and OS ( P  = .06). There was one grade‐5 toxicity due to carotid rupture. Conclusions: IORT has shown effective LRC and OS with an acceptably low rate of severe toxicity at our institution. OS was significantly better for non‐SCC histology. For SCC patients, there is a trend toward improved PFS and OS associated with negative surgical margins.